Teoretyczne i metodyczne implikacje komunikacji marketingowej w Europie wielu kultur językowych - Światowy, Grażyna (Theoretical and Methodological Implications of Marketing Communication in Multicultural and Multilingual Europe, 2008)
The paper is an introduction to problems addressed at the conference, demonstrating the role of communication as human interaction aimed at completion of personal, public and economic goals. In the face of increased competition and rivalry, continuous improvement of intellectual competence is a particularly important issue, especially in regard to skilful and efficient communication. This challenge relates also to building the European knowledge society, as one of priorities of the EU social policy. The EU framework supports multiple programs for development of sciences and education in regard to culture and language. Theoretical divagations help clarify key concepts of the subject, as well as various models of communication and their practical application. The author outlines methodical issues of the subject: how to teach, measure and study linguistic competence in the context of cultural determinants, and how to cope with psychological barriers of informational perception.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 13-24